Evaluating wetland condition in urban Denver - Smith, Gabrielle, speaker; Kuhn, Bernadette, speaker; Smith, Pam, speaker; Sueltenfuss, Jeremy, speaker; Anderson, David, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
Denver's urban wetlands are poorly mapped, understudied as critical wildlife habitat, and perpetually subject to frequent anthropogenic disturbance. As Denver County continues to lead the state in population growth, current information on the location and status of these wetlands is needed for city planners, land managers, and the public to prioritize conservation and restoration efforts. Our team conducted field-based wetland assessments at 27 sites within Denver County, as well 4 several locations in Denver's Mountain Parks. We used NatureServe's Environmental Integrity Assessment framework, a multi-metric index based on four major scoring categories: landscape context, biotic condition, hydrologic condition, and physiochemical condition. In addition, we used 2010 color infrared imagery to create an updated National Wetland Inventory GIS layer of wetlands in Denver County. NWI maps have not been updated for the County since 1985. We used our results to create a list of prioritized wetlands for conservation and restoration. Despite the poor ecological condition of most sites, our team identified urban wetlands with high plant diversity, rare plant species, and even a rare amphibian occurrence. Our results suggest that although the majority of these wetlands are highly disturbed, they provide critical refuges for wildlife and plant diversity in an otherwise developed landscape.
Moderator: David Anderson.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Presenter: Bernadette Kuhn.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses